Multimedia foundations core concepts for digital design - Costello, Vic (New York Routledge, 2017)
Understand the core concepts and skills of multimedia production and digital storytelling using text, graphics, photographs, sound, motion, and video. Then, put it all together using the skills that you have developed for effective project planning, collaboration, visual communication, and graphic design. Presented in full color with hundreds of vibrant illustrations, Multimedia Foundations, second edition trains you in the principles and skill sets common to all forms of digital media production, enabling you to create successful, engaging content, no matter what tools you are using. The second edition has been fully updated and features a new chapter on video production and new sections on multimedia storytelling, mobile screen layouts and interface design, HD DSLR video/filmmaking, and motion graphics/animation. The companion website, which features a wealth of web resources, glossary terms, and video tutorials, has also been updated with new content for both students and instructors.
Understanding multimedia -- The computer -- Project planning and evaluation -- Visual communication -- Page layout -- User interface design -- Web design -- Text -- Graphics -- Photography -- Recording formats and device settings -- Audio production -- Video production -- Time-based editing.
Includes index.
Keywords: Multimedia systems; Digital media